2023
DOI: 10.1002/adfm.202300365
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Intercalation Supramolecular Structure for Photocatalytic CO2 Reduction to Ethylene Under Visible Light

Abstract: Photocatalytic CO2 reduction (CO2PR) into multi‐carbon products (especially C2H4) is a highly attractive route for global carbon cycle, however, which is seriously limited by sluggish C‐C coupling kinetics and competitive hydrogen evolution reaction (HER) and so on. Herein, the fabrication of a novel supramolecular assembly of NiAl‐Fe‐TCPP is reported by intercalating iron porphyrin (Fe‐TCPP) into NiAl‐layered double hydroxide (NiAl‐LDH), and the resultant NiAl‐Fe‐TCPP exhibit superior catalytic performance on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Chemie depict that LaCu/CN displays the most quenched intensity and thus the lowest recombination of photogenerated carriers. [19] Furthermore, LaCu/CN also exhibits significantly enhanced photocurrent response compared with that of CN, La/CN, and Cu/CN, as displayed in the photocurrent-time curves (Figure 3e). In addition, electrochemical impedance spectroscopy measurements show the smallest interfacial resistance of LaCu/CN (Figure S14), suggesting its fastest interfacial charge transport.…”
Section: Methodsmentioning
confidence: 87%
“…Chemie depict that LaCu/CN displays the most quenched intensity and thus the lowest recombination of photogenerated carriers. [19] Furthermore, LaCu/CN also exhibits significantly enhanced photocurrent response compared with that of CN, La/CN, and Cu/CN, as displayed in the photocurrent-time curves (Figure 3e). In addition, electrochemical impedance spectroscopy measurements show the smallest interfacial resistance of LaCu/CN (Figure S14), suggesting its fastest interfacial charge transport.…”
Section: Methodsmentioning
confidence: 87%
“…The ion exchange method is particularly effective in the preparation of noncarbonate intercalated LDHs, as it allows for the incorporation of diverse organic (e.g., dodecylsulfate, metalloporphyrin, benzoate) and inorganic (e.g., CO 3 2– , NO 3 – , Br – , ClO 4 – , Cl – , SO 4 ) anions into the Ni-based LDH interlayer. For example, Li et al employed this method to synthesize NiAl-LDH with intercalated Cl – and NO 3 – ions.…”
Section: Synthetic Methodologymentioning
confidence: 99%
“…Doping engineering has enabled the construction of homogeneous and abundant atomic-level catalytic sites for photocatalytic CO 2 reduction with improved target product selectivity. , Cu species have been widely used as co-catalysts to improve the CO 2 reduction performance due to their special adsorption and activation ability to CO 2 . Notably, as for the aqueous photocatalytic CO 2 reduction system, proton reduction to H 2 presents a hardly avoidably competitive process. Under such circumstances, it has been found that when Cu species are introduced to modify semiconductors, the photocatalytic CO 2 reduction performance is indeed enhanced and notably, the H 2 evolution rate is simultaneously promoted. , This is mainly ascribed to the fact that the photoelectrons with a prolonged lifetime induced by Cu doping indiscriminately reduce CO 2 molecules and protons. Such a situation limits the overall CO 2 reduction yield .…”
Section: Introductionmentioning
confidence: 99%